Sensitivity of total column NO2 at a marine site within the Chesapeake Bay during OWLETS-2. (15th May 2022) - Kotsakis, Alexander; Sullivan, John T.; Hanisco, Thomas F.; Swap, Robert J.; Caicedo, Vanessa; Berkoff, Timothy A.; Gronoff, Guillaume; Loughner, Christopher P.; Ren, Xinrong; Luke, Winston T.; Kelley, Paul; Stratton, Phillip R.; et al.
Abstract: In coastal environments like the Chesapeake Bay, the presence of the sea/bay breeze circulation can contribute to poor air quality and makes modeling the meteorological and chemical impacts of the sea/bay breeze in air quality forecast models a challenge. The Ozone Water-Land Environmental Transition Study 2 field campaign aimed to better quantify the mechanisms affecting surface, profile, and columnar trace gas amounts between the land and water. Using HYSPLIT back trajectory modeling, the meteorological variability affecting Pandora NO2 and surface O3 was quantified. Clustered back trajectories showed that westerly and north-northwesterly winds resulted in the highest MDA8 ozone values over the study domain. An analysis of multiday ozone event, demonstrated how TROPOMI can capture the spatial variability of NO2 observed by the Pandora network, including the accumulation of NO2 over the Chesapeake Bay. VOC measurements during multiday ozone event were analyzed and sources of ozone precursors, such as a coal fire power plant, were identified. Further investigation of the surface ozone data at HMI revealed that significant amounts of ozone were maintained over the Chesapeake Bay at night. Using a combination of ozone lidar, Pandora, in situ O3 and NO2, and wind lidar measurements, a lofted plume of NO2 was detected over water. Additionally, the same suite of observations found significant differences in the horizontal and vertical extent of ozone on the highest exceedance day of the event. Surface measurements of trace gases (NO2 and O3 ) can vary significantly from remote sensing (Pandora, TROPOMI, O3lidar), highlighting the need for sensitive profile, columnar, and in situ measurements in complex urban, marine environments for future geostationary air quality validation. Highlights: Clustered back trajectories showed that westerly & northwesterly winds resulted in the highest ozone values. TROPOMI captured the spatial variability of NO2 observed by the Pandora network, including accumulation of NO2 over water. Configuration of O3 lidar, Pandora, wind lidar, and in situ measurements, detected lofted plumes of NO2 and O3 over water.